Assembling laminated films via the synchronous reduction of graphene oxide and formation of copper-based metal organic frameworks. Issue 1 (4th December 2018) - Li, Li; Chen, Ruyi; Gong, Yujiao; Yu, Chenyang; Hui, Zengyu; Xu, Hai; Zhao, Xi; Sun, Yue; Zhao, Wen; Sun, Gengzhi; Huang, Wei
Abstract : A free-standing laminated hybrid film is prepared via the synchronous reduction of graphene oxide and formation of copper-based metal organic frameworks. Abstract : Metal organic frameworks (MOFs) with small particle sizes and incorporated redox sites have attracted tremendous attention as promising electrode materials in supercapacitors (SCs). However, their wide adoption is seriously limited by their poor conductivity and complicated preparation route. Herein, we report a low-cost, single-step method to assemble free-standing laminated hybrid films via the synchronous reduction of graphene oxide (GO) and formation of copper-based MOFs. During this process, small Cu-MOF nanoparticles (NPs) with a mean diameter of 50 nm are in situ embedded in reduced graphene oxide (rGO) to overcome the insulating problem of MOFs and the restacking of the rGO nanosheets. Due to the positive synergistic effects between Cu-MOF crystals and rGO nanosheets, the hybrid Cu-MOF/rGO film electrode delivers a high specific capacitance of 1871 F g −1 at 0.5 A g −1 and a good electrochemical stability with 89% retention after 5000 charge–discharge cycles.